A gatinha branca - Testa, Ivanete Maria; Cardoso, Sinara Cristiane Fritsch; Nascimento, Cleide Dias do; Bordinhão, Andréia Jonceline Chiozini; Simião, Regina Aparecida Versoza (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf